Resistance or Acceptance? The Voice of Local Cross-Border Organizations in Times of Re-Bordering - Svensson, Sara (Journal of borderlands studies, 2022)
National borders in Europe are increasingly subject to re-bordering processes, including the external and internal borders of the European Union. This article asks if and how local cross-border organizations (Euroregions) have reacted to to the recent hardening of these borders. The Austrian-German border is one where border controls have been re-introduced in the wake of the 2015 refugee crisis, and which also has significant local cross-border institutional activity. Based on an analysis of 350 written items, published by six Euroregions during the five-year period 2015-2019, the article finds that the Euroregions have generally not voiced resistance to this development and have not been active in relation to the policy field of refugee or migrant inclusion. When they reacted, the resistance has mainly been embedded in an argumentation linked to instrumental concerns, such as the traffic situation, even though the research also demonstrated the existence of normative arguments related to human rights discourses and rights of migrants.